Building Trust in Hyperconnected World - Mingmanee, Narathon; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
In today’s hyperconnected world, trust has become a cornerstone for success, both in business and governance. The rapid digitalization of everyday life, particularly due to advancements in communication technologies, has fundamentally changed the way individuals, governments, and institutions interact. This paper explores the role of trust in the hyperconnected world and how governments and organizations can foster it. Drawing upon the theoretical insights of Assoc. Prof. Wasan Luangprapat and case studies from Thailand, the paper highlights the challenges faced by governments in fostering trust among diverse target groups. It argues that the government must act as a solution enabler, providing timely support and actively engaging society to build trust, especially among vulnerable populations such as the elderly. Using a qualitative research approach, data from surveys of different demographic groups are analyzed to assess levels of trust in digital public policies. The results reveal that while digitalization has improved communication and access to services, it has also introduced challenges in ensuring inclusivity and fairness, particularly in areas like elder care. The findings underscore the importance of tailoring government policies to specific groups to build long-term trust in a hyperconnected society. The paper concludes with recommendations for governments to improve policy frameworks to better address the evolving needs of society, emphasizing inclusivity, timely problem resolution, and communication improvements in public services.